2013 IEEE International Conference on Computer Vision 2013
DOI: 10.1109/iccv.2013.73
|View full text |Cite
|
Sign up to set email alerts
|

Structured Light in Sunlight

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…Energy-efficient codes for redistributive projectors: Of course, between the two extremes of ideal impulse projection (minimum redistribution ratio) and conventional mask-based projection (maximum redistribution ratio) lies a whole spectrum of arrangements that redistribute light partially [Hoskinson et al 2010;Mertz et al 2012;Gupta et al 2013;Damberg and Heidrich 2015]. We explore this spectrum briefly through simulations, noting that a rapid "phase transition" seems to occur in our energy-efficient codes, with pure impulses on one end switching to dense codes on the other.…”
Section: Energy-efficient Codes By Homogeneous Factorizationmentioning
confidence: 98%
See 1 more Smart Citation
“…Energy-efficient codes for redistributive projectors: Of course, between the two extremes of ideal impulse projection (minimum redistribution ratio) and conventional mask-based projection (maximum redistribution ratio) lies a whole spectrum of arrangements that redistribute light partially [Hoskinson et al 2010;Mertz et al 2012;Gupta et al 2013;Damberg and Heidrich 2015]. We explore this spectrum briefly through simulations, noting that a rapid "phase transition" seems to occur in our energy-efficient codes, with pure impulses on one end switching to dense codes on the other.…”
Section: Energy-efficient Codes By Homogeneous Factorizationmentioning
confidence: 98%
“…The near end of the range, with σ = 1, represents an idealized projector that is perfectly efficient (Figure 2b). This projector can send all its light through just one pixel for the entire exposure time T but can also distribute it-without any blocking-according to an arbitrary illumination l. Between these two extremes lies a whole spectrum of projection technologies that approach this ideal to a greater or lesser extent [Hoskinson et al 2010;Gupta et al 2013;Damberg et al 2014;Damberg and Heidrich 2015].…”
Section: Redistributive Projection and Sensor Maskingmentioning
confidence: 99%
“…In addition, light transport techniques have been very successful for the challenging problem of 3-D scanning of translucent objects [25,20] and high quality structured light scanning [36,13,37,14].…”
Section: Light Transport Acquisitionmentioning
confidence: 99%
“…However, the main drawback of such IR-projector-based sensors is their inability to work outdoors and their power consumption. Authors of [24] also showed the degradation of the 3D reconstruction at different times of the day. The stronger the illuminance, the poorer the quality of the resulting 3D map.…”
Section: Stereo Camerasmentioning
confidence: 99%
“…Our previous study assessed that the scenes illuminance affects the quality of the resulting depth maps [4]. While RGBD cameras are unable to work under bright sunlight [24], passive stereo cameras' performance drastically drops under low or bright illumination unless the sensors have a high dynamic range. Our approach works on depth maps which are not completely dense.…”
Section: Resolution Studymentioning
confidence: 99%